(untitled) (Research, Society and Development, 2021)
Typical product of the Brazilian northeast, the coalho type cheese has a great economic and cultural importance for this region. In the state of Paraíba, it represents a significant means of income generation for milk producers, most of them producing cheeses like curds in an artisanal way. Therefore, raw milk is used as the main raw material for the manufacture of this delicacy, so used in northeastern gastronomy. The lack of use of pasteurization methods of the food matrix becomes a favorable means for the dissemination of product contamination. the absence of good manufacturing practices, associated with inadequate transportation, packaging and marketing, leaves consumers exposed to the risk of foodborne illnesses. due to the economic and cultural importance in the trade of this product in the evaluated city, this study aimed to analyze the microbiological quality of the artisanal rennet cheese sold at the fair. Thus, 10 samples from different commercial points of the cheese fair in the city of Campina Grande, Paraíba, were analyzed. Microbiological analyzes followed the protocol of current legislation for this product, where they were evaluated for the presence of total coliforms, Staphylococcus aureus, Salmonella spp. and Listeria monocytogenes. Most of the samples analyzed were above what is allowed by the regulations for total coliforms, Salmonela spp. and Listeria monocytogenes. From the results of the microbiological analyses, inadequacies of the microbiological standards of the coalho cheese sold at the central fair were demonstrated, as it presents a large amount of pathogenic microorganisms above the limit required by Brazilian legislation, which raises a public health alert.